Epidemiology, use, and practice of the intraosseous route in an out-of-hospital emergency department: a retrospective cross-sectional study - Burgos-Esteban, Amaya; Quintana-Diaz, Manuel; Cordón-Hurtado, Valvanera; Giménez-Luzuriaga, Marta; Santolalla-Arnedo, Iván; de Viñaspre-Hernández, Regina Ruiz; Gea-Caballero, Vicente; Santos-Sánchez, Jose Angel; Navas-Echazarreta, Noelia; Rodríguez-Calvo, Antonio; Sánchez-Conde, Pilar; Juárez-Vela, Raúl (Frontiers in Public Health, 2024)
The Spanish Emergency Medical Services, according to the model we know today, were formed during the 80s and 90s of the 20th centuries. The Health Emergency Service (SES), 061 La Rioja, began to to assist the population of La Rioja in November 1999. An essential part of the mission of The SES is the provision of care and the transfer of critical patients using advanced life support techniques. In daily practice, out-of-hospital emergency services are faced with situations in which they must deal with the care of serious or critically ill patients, in which the possibility of being able to channel peripheral vascular access as part of advanced life support quickly may be difficult or impossible. In these cases, cannulation of intraosseous vascular access may be the key to early and adequate care. This study aimed to determine the incidence of the use and epidemiology use of intraosseous vascular access in the SES 061 La Rioja during the year 2022. We performed an observational retrospective cross-sectional studies was conducted during 2022. It included a population of 4.364 possible patients as a total of interventions in the community of La Rioja in that year. 0.66%, presented a clinical situation that required the establishment of intraosseous vascular access to enable out-of-hospital stabilization, this objective was achieved in 41.3%. Stabilized 26.1% of patients who presented cardiorespiratory arrest (CA) and 100% presented shock and severe trauma. Intraosseous vascular access provides a suitable route for out-of-hospital stabilization of critically ill patients when peripheral vascular access is difficult or impossible.